2003
DOI: 10.1159/000070361
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and Differential Validity of Alexithymia and Depression: A Comparison of the Toronto Alexithymia and Self-Rating Depression Scales

Abstract: Theoretically, the constructs of alexithymia and depression share many common characteristics. Empirically moderate correlations between measures of alexithymia and depression have been found, hence it has been argued that the Toronto Alexithymia Scale (TAS) may be, at least in some part, just another measure for depression. The purpose of this study was to evaluate the construct validity of alexithymia and to analyze the relationship between alexithymia and depression. Exploratory and confirmatory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
3
15
0
2
Order By: Relevance
“…These results do not mean, however, that depression and alexithymia are overlaping dimensions. Factor analyses showed that alexithymia and depression are not simply different measures of the same underlying construct [56]. Significant positive correlations were also found between anxiety and total alexithymia scores, but the relationship was less consistent across factors, with a systematic relationship for DIF, no relationship at all for EOT, and one out of two correlations significant for DDF.…”
Section: Relationship Between Alexithymia Depression and Anxietymentioning
confidence: 87%
“…These results do not mean, however, that depression and alexithymia are overlaping dimensions. Factor analyses showed that alexithymia and depression are not simply different measures of the same underlying construct [56]. Significant positive correlations were also found between anxiety and total alexithymia scores, but the relationship was less consistent across factors, with a systematic relationship for DIF, no relationship at all for EOT, and one out of two correlations significant for DDF.…”
Section: Relationship Between Alexithymia Depression and Anxietymentioning
confidence: 87%
“…One of the virtues of the study was the ecological validity (see, in this context, Müller et al [36] ). Subjects were patients in an intake interview who interacted with their assigned therapist without any additional constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Elle n'a pu être établie qu'en comparant les scores des différentes composantes du questionnaire à des [21,25]. Ce sont des études longitudinales contrôlant l'évolution des variables émotionnelles négatives, en particulier pendant une dépression, qui ont permis de soutenir la stabilité de l'alexithymie [18,26].…”
Section: Autres Indices De Validitéunclassified